Genetic differentiation and phylogeography of rotifer Polyarthra dolichoptera and P. vulgaris populations between Southeastern China and eastern North America: High intercontinental differences. Issue 5 (13th May 2022) - Liang, Diwen; McManus, George B.; Wang, Qing; Sun, Xian; Liu, Zhiwei; Lin, Senjie; Yang, Yufeng
Abstract: Genetic differentiations and phylogeographical patterns of small organisms may be shaped by spatial isolation, environmental gradients, and gene flow. However, knowledge about genetic differentiation of rotifers at the intercontinental scale is still limited. Polyarthra dolichoptera and P . vulgaris are cosmopolitan rotifers that are tolerant to environmental changes, offering an excellent model to address the research gap. Here, we investigated the populations in Southeastern China and eastern North America and evaluated the phylogeographical patterns from their geographical range sizes, geographic–genetic distance relationships and their responses to spatial‐environmental factors. Using the mitochondrial cytochrome c oxidase subunit I gene as the DNA marker, we analyzed a total of 170 individuals. Our results showed that some putative cryptic species, also known as entities were widely distributed, but most of them were limited to single areas. The divergence of P . dolichoptera and P . vulgaris indicated that gene flow between continents was limited while that within each continent was stronger. Oceanographic barriers do affect the phylogeographic pattern of rotifers in continental waters and serve to maintain genetic diversity in nature. The genetic distance of P . dolichoptera and P . vulgaris populations showed significant positive correlation with geographic distance. This might be due to the combined effects of habitat heterogeneity, long‐distance colonization, and oceanographic barriers. Furthermore, at the intercontinental scale, spatial distance had a stronger influence than environmental variables on the genetic differentiations of both populations. Wind‐ and animal‐mediated transport and even historical events of continental plate tectonics are potential factors for phylogeography of cosmopolitan rotifers. Abstract : Oceanographic barriers affect the phylogeographic pattern of rotifers in continental waters and maintaining genetic diversity in nature. The divergence indicates that gene flow between eastern North America and Southeastern China is limited while that within eastern North America or Southeastern China was higher. Spatial variables are key factors in affecting the genetic differentiation of rotifers when compared with environmental variables on the intercontinental scale.